2011
DOI: 10.3389/fpsyg.2011.00146
|View full text |Cite
|
Sign up to set email alerts
|

Native Experience with a Tone Language Enhances Pitch Discrimination and the Timing of Neural Responses to Pitch Change

Abstract: Native tone language experience has been linked with alterations in the production and perception of pitch in language, as well as with the brain response to linguistic and non-linguistic tones. Here we use two experiments to address whether these changes apply to the discrimination of simple pitch changes and pitch intervals. Event related potentials (ERPs) were recorded from native Mandarin speakers and a control group during a same/different task with pairs of pure tones differing only in pitch height, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
62
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 52 publications
(77 reference statements)
12
62
0
Order By: Relevance
“…Comparisons between language groups allowed us to assess whether tone language speakers show a hemispheric specialization for contour and interval processing. Consistent with previous neurophysiological studies (Gandour et al, 2000;Chandrasekaran et al, 2007;Giuliano et al, 2011;Bidelman and Lee, 2015), we expected to observe enhanced pitch MMNs in Chinese listeners across the board. Additionally, based on previous behavioral and lesion data (Peretz, 1990;Lie´geois-Chauvel et al, 1998), we expected to find that the cortical encoding of pitch contour and interval in Chinese listeners is dominated by neural mechanisms of the right and left hemisphere, respectively.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…Comparisons between language groups allowed us to assess whether tone language speakers show a hemispheric specialization for contour and interval processing. Consistent with previous neurophysiological studies (Gandour et al, 2000;Chandrasekaran et al, 2007;Giuliano et al, 2011;Bidelman and Lee, 2015), we expected to observe enhanced pitch MMNs in Chinese listeners across the board. Additionally, based on previous behavioral and lesion data (Peretz, 1990;Lie´geois-Chauvel et al, 1998), we expected to find that the cortical encoding of pitch contour and interval in Chinese listeners is dominated by neural mechanisms of the right and left hemisphere, respectively.…”
Section: Introductionsupporting
confidence: 85%
“…This inconsistency presumably results from the fact that laterality effects are either too subtle to detect via ERPs or that they occur in processing stages after the automatic generation of the MMN (Trainor et al, 2002;Fujioka et al, 2004). However, previous studies have demonstrated that both cortical (Gandour et al, 2000;Chandrasekaran et al, 2007;Giuliano et al, 2011) and subcortical (Bidelman et al, 2011a,b) neural activity is modulated by long-term experience with a tone language (e.g., Mandarin Chinese). While all languages use pitch for suprasegmental linguistic distinctions (e.g., stress, intonation), tone languages are unique in that pitch is used to make lexical distinctions at the word level.…”
Section: Introductionmentioning
confidence: 88%
“…In nonmusicians, only one hub was located in peri-sylvian language regions. This indicates, therefore, a tendency at least toward more local clustering in the peri-sylvian brain area in RP musicians and supports the hypothesis that the brain of musicians is partly prepared to process auditory language information differently (see, for further support of this hypothesis, the special issue on the relation between music and language; Ettlinger, Margulis, & Wong, 2011;Giuliano, Pfordresher, Stanley, Narayana, & Wicha, 2011;Ott, Langer, Oechslin, Meyer, & Jäncke, 2011;Patel, 2011;Schon & Francois, 2011).…”
Section: Discussionsupporting
confidence: 51%
“…Previous work suggests individuals vary considerably with respect to the vocal imitation of sung pitch (Berkowska & Dalla Bella, 2009;Dalla Bella, Berkowska, & Sowinski, 2011;Pfordresher, 2011;Pfordresher & Brown, 2007;Pfordresher & Mantell, 2009;Pfordresher et al, 2010;Welch, 1979), and further evidence suggests that such "poor-pitch" singers may have difficulty transferring from one sequence to anther, given that they exhibit a tendency (not seen in accurate singers) to make pitch errors that drift in the direction of their own comfortable pitch range (Pfordresher & Brown, 2007). Poor-pitch singers may have similar difficulty imitating speech (Mantell & Pfordresher, 2013), in line with integrationist views of music and language.…”
Section: Individual Differencesmentioning
confidence: 99%